Development of Learner Worksheets Assisted by Geogebra Software on Trigonometry Material for Class X - Mesaluna Rida Hapsari; Adi Nurcahyo; Muhamad Toyib (Journal of Medives: Journal of Mathematics Education IKIP Veteran Semarang, 2024)
This study aims to describe the validity, practicality, and effectiveness of trigonometry learning media in improving students' understanding of concepts and skills in mathematics. The development method used is the Research and Development (R&D) method. The model used in this research is the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of this study indicate that the validity test results by validators with a total average of 0.75, which means valid because it is in the index 0.4 ? V ? 0.8, which means it has high validity criteria. Then, a paired sample T-test was conducted to determine whether there was a significant difference before and after using the media and the resulting sig. (2-tailed) is 0.000 because of the sig value. <0.05, then H0 is rejected, meaning there is a significant difference between the pre-test and post-test results of students' ability to solve trigonometry material questions. So, it can be concluded that using LKPD assisted by Geogebra Software has proven effective in increasing students' interest in learning and involvement in learning mathematics and increasing students' understanding of trigonometric concepts, making the learning process more exciting and interactive.